1996
DOI: 10.1021/jm960058h
|View full text |Cite
|
Sign up to set email alerts
|

Principal Components Describing Biological Activities and Molecular Diversity of Heterocyclic Aromatic Ring Fragments

Abstract: Ten physicochemical variables have been calculated for each of 100 different aromatic rings. These variables were selected because of their potential involvement in the molecular recognition of drug-receptor binding interactions, and they include size, lipophilicity, dipole magnitude and orientation, HOMO and LUMO energies, and electronic point charges. A total of 59 different aromatic ring systems were studied including monocyclics and [5.5]-, [6.5]- and [6.6]-fused bicyclics. A principal components analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Some of descriptors may be correlated to each other. For the prevention of repeating descriptors and classifying them, we have used principal component analysis (PCA) [39]. PCA involves a mathematical procedure that transforms a number of (possibly) correlated variables into a (smaller) number of uncorrelated variables called principal components (PCs).…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of descriptors may be correlated to each other. For the prevention of repeating descriptors and classifying them, we have used principal component analysis (PCA) [39]. PCA involves a mathematical procedure that transforms a number of (possibly) correlated variables into a (smaller) number of uncorrelated variables called principal components (PCs).…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
“…In previous work [34] we also showed that volume decreases the logK I while here we obtained several descriptors which show a size property. Factor 2 includes L/BW, RGYR, SPH, ASP and FDI which belong to geometrical and HOMA and AROM which belong to aromaticity indices [39]. Aromaticity descriptors (HOMA, HOMT, RCI, AROM, ARR) distribute between three factors, because aromaticity depends on size, electronic properties and molecular shape.…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%
“…For medicinal chemists, this may be of little help since, as already mentioned, it is well known that the properties of a heterocyclic ring heavily depend on its substitution position. In a study recently published by McGuire et al [32], this question has been raised; they characterized a total of 59 different aromatic ring systems appearing in a total of 100 isomers using a total of 10 classical QSAR parameters, together with multivariate data analysis. The limited number and also the nature of the parameters used in this study, however, may cast doubt on the general applicability of the PCs obtained.…”
Section: Characterization Of Heteroaromatic Residuesmentioning
confidence: 99%
“…Our methods could be adapted to the design exclusively of oral drugs, but that was not our objective: not all targets of interest require oral drugs, and indeed oral activity is not a prerequisite during all the stages of drug discovery and research. Descriptors previously described by McGuire and coworkers [8] were adapted to determine the similarity or diversity of heterocycles and can be applied to this set of compounds to enable suitable choices to be made for drug and library design purposes, in conjunction with the frequency with which each heterocycle is found in the late-phase drug molecules studied here.…”
Section: Introductionmentioning
confidence: 99%